Colloidal interactions and unusual crystallization versus de-mixing of elastic multipoles formed by gold mesoflowers - Ye Yuan (Nature Portfolio, 2020)
Elasticity-mediated particle interaction in a hosting medium holds promise for material engineering of unusual structures. Yuan et al. show that the gold microparticles can induce elastic multipoles of different symmetries when dispersed in a nematic liquid crystal as building blocks for various crystals.